Expanding therapeutic horizons: glucagon-like peptide-1 receptor agonists and sodium glucose transporter-2 inhibitors in poly cystic ovarian syndrome: a comprehensive review including systematic review and network meta-analysis of randomized clinical trials - Kannan Sridharan; Gowri Sivaramakrishnan (Diabetology & Metabolic Syndrome)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex endocrine characterized by hyperandrogenism, hormonal imbalances, and metabolic disruptions, leading to reproductive complications and increased risk of cardiometabolic diseases. While lifestyle modifications are the cornerstone of PCOS management, pharmacological interventions, including metformin, oral contraceptives, and anti-androgens, are commonly utilized. Recently, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and sodium-glucose cotransporter-2 inhibitors (SGLT2is) have shown promising results in PCOS management. Methods This study conducted a comprehensive review of randomized clinical trials evaluating the effects of GLP-1 RAs and SGLT2is in women with PCOS. A systematic literature search was performed, and network meta-analysis using random-effects model that generated mixed treatment comparison estimates was employed to assess the comparative efficacy of these drug classes on clinical (menstrual frequency, pregnancy rate and proportion of patients with regular menstrual cycles), anthropometric, hormonal, and metabolic parameters. Additionally, a systematic review of preclinical studies investigating GLP-1 RAs and SGLT2is in animal models of PCOS was undertaken. Results This comprehensive meta-analysis included 27 RCTs (1642 participants). GLP-1 RAs (alone and in combination with metformin) were observed to improve menstrual frequencies. GLP-1 RAs showed significant reductions in all anthropometric parameters, while SGLT2is was observed to improve wait hip ratio (WHR) and android gynoid fat (AGF) ratio (in addition to reduced body weight observed with SGLT2is/metformin combination). Reductions in WHR and AGF ratio were better with SGLT2is compared to GLP-1 RAs. The combination of GLP-1 RAs and SGLT2is was observed to have superior efficacy in reducing body weight, percent fat mass, and AGF ratio compared to GLP-1 RAs alone. Regarding hormonal parameters, GLP-1 RAs were observed with significant improvement in free androgen index (FAI), free testosterone, androstenedione, and sex hormone binding globulin levels. SGLT2is was observed with significant improvements in FAI and total testosterone, outperforming GLP-1 RAs in reducing these parameters. Regarding metabolic parameters, GLP-1 RAs significantly improved triglycerides, markers of insulin resistance and fasting and postprandial plasma glucose. SGLT2is was associated with significant improvements in homeostatic model assessment for insulin resistance (HOMA-IR) and fasting plasma glucose, and in combination with metformin, SGLT2is significantly improved triglycerides. SGLT2is outperformed GLP-1 RAs in reducing LDL cholesterol and HOMA-IR. The combination of SGLT2is and GLP-1 RAs was better than GLP-1 RAs in reducing triglycerides and fasting plasma glucose. However, the strength of evidence for these findings was very low. Systematic assessment of animal studies revealed a potential association of several molecular pathways, including AMPK-α, SIRT1, FDX, PI3K/AKT, endothelial adhesion molecules (VCAM, ICAM, and E-selectin), STAR, and CYP17A1, with the therapeutic effects of GLP-1 RAs and SGLT2is in PCOS. Both drug classes were associated with significant improvements in ovarian morphology in animal studies. Conclusion This systematic review and meta-analysis advance our understanding of GLP-1 RAs and SGLT2is in PCOS management. While both drug classes demonstrate efficacy in metabolic parameters, their distinct mechanisms offer unique therapeutic advantages. SGLT2is excel in improving hormonal profiles and insulin resistance, whereas GLP-1 RAs show consistent benefits in weight management. The enhanced efficacy of combination therapy suggests a potential paradigm shift in PCOS treatment strategies, moving beyond traditional monotherapy approaches. These findings support the therapeutic potential of both drug classes, individually or combined, in PCOS management, providing a foundation for more personalized treatment approaches.